Edwardsiella tarda Sip2: A Serum-Induced Protein That Is Essential to Serum Survival, Acid Resistance, Intracellular Replication, and Host Infection - Li, Mo-fei; Sun, Li (Frontiers in Microbiology, 2018)
Edwardsiella tarda is a broad-host pathogen that can infect mammals, reptiles, and fish. E. tarda exhibits a remarkable ability to survive in host serum and replicate in host phagocytes, but the underlining mechanism is unclear. In this study, in order to identify E. tarda proteins involved in serum resistance, iTRAQ proteomic analysis was performed to examine the whole-cell protein profiles of TX01, a pathogenic E. tarda isolate, in response to serum treatment. Of the differentially expressed proteins identified, one (named Sip2) possesses a conserved hydrogenase domain and is homologous to the putative hydrogenase accessory protein HypB. When Sip2 was expressed in Escherichia coli, it significantly enhanced the survival of the host cells in serum. Compared to TX01, the sip2 knockout, TX01sip2, was dramatically reduced in the ability of hydrogenase activity, serum resistance, intracellular replication, dissemination in fish tissues, and causing mortality in infected fish. The lost virulence capacities of TX01sip2 were restored by complementation with the sip2 gene. Furthermore, TX01sip2 was significantly reduced in the capacity to grow under low pHs and iron-depleted conditions, and was unable to maintain its internal pH in acidic environment. Taken together, these results indicate that Sip2 is a novel serum-induced protein that is essential to serum resistance, cellular and tissue infection, and coping with acidic stress via its ability to modulate intracellular pH.